2015
DOI: 10.4269/ajtmh.15-0353
|View full text |Cite
|
Sign up to set email alerts
|

Anemia Among Children Exposed to Polyparasitism in Coastal Kenya

Abstract: Abstract. Anemia represents a substantial problem for children living in areas with limited resources and significant parasite burden. We performed a cross-sectional study of 254 Kenyan preschool-and early school-age children in a setting endemic for multiple chronic parasitic infections to explore mechanisms of their anemia. Complete venous blood cell counts revealed a high prevalence of local childhood anemia (79%). Evaluating the potential links between low hemoglobin and socioeconomic factors, nutritional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
(45 reference statements)
1
9
2
Order By: Relevance
“…33 These findings suggest that ID may not be the principal cause of anemia in children under 5 years of age in the African Great Lake Region. The results are in contrast with findings in other developing countries including Kenya where 84% of anemic children (preschool and early school children) from coastal region had evidence of IDA, 34 and Côte d'Ivoire where 80% of anemic preschool children had IDA. 35 This low ID in our sample is surprising given the high proportion of undernourished children and the absence of a public health intervention that primarily targets ID.…”
Section: Discussioncontrasting
confidence: 99%
“…33 These findings suggest that ID may not be the principal cause of anemia in children under 5 years of age in the African Great Lake Region. The results are in contrast with findings in other developing countries including Kenya where 84% of anemic children (preschool and early school children) from coastal region had evidence of IDA, 34 and Côte d'Ivoire where 80% of anemic preschool children had IDA. 35 This low ID in our sample is surprising given the high proportion of undernourished children and the absence of a public health intervention that primarily targets ID.…”
Section: Discussioncontrasting
confidence: 99%
“…Concomitant Plasmodium and helminth (S. haematobium and STHs) infections are common in parts of South-West Cameroon (8,36,37), due to geographic overlap of climatic and socio-economic conditions that support survival of the malaria parasite vectors, egg and larval development of Polyparasitism occurred in 19.9% of the children although the prevalence of single infection was more common with similar occurrence of S. haematobium and P. falciparum infection. This polyparasitism prevalence in SAC is higher than the 7.6% observed in Mbam and Inoubou Division, within the Centre Region of Cameroon [38], 11.2% in Ghana [39] and lower than the 30% and 28% observed in Kenya [40,41]. When compared with previous studies in the same locality [25,42], a decline in infections with S. haematobium and P. falciparum following MDA was observed in SAC.…”
Section: Discussioncontrasting
confidence: 64%
“…Our findings further validate the correlation between malarial infection and childhood anemia in southeastern Kenya. 8 Current STH infection was also associated with significantly diminished current Hb, and any infection in the postnatal or current period was linked to lower Hb levels. Together, these data emphasize the need to treat and prevent parasitic infections, during both pregnancy and early childhood, to limit the anemia of early childhood.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study conducted in nearby Jego, Kenya, among children aged 3–11 years with high rates of parasitic infections found that childhood anemia prevalence was 79% and asymptomatic malaria infection was one of the strongest correlates. 8 That study concluded that anemia of inflammation and iron deficiency are both significant sources of childhood anemia, and emphasized the need to address both to properly manage childhood anemia. 8 However, children younger than 2 years, who are most vulnerable to the deficiency linked to anemia, were not included in that study.…”
Section: Discussionmentioning
confidence: 99%